Effect of mould tilt angle on the mechanical properties of as-cast aluminum alloy - Hamzah, E.; Prayitno, D.; Ghazali, M. Z. M. (Elsevier B V, 2002)
A near-net shape-casting technique to produce as-cast aluminum-silicon alloy metal bars has been designed and used in fabrication. In this technique, molten aluminum alloy was poured from a moving tundish into the D-shaped groove of a tilted copper mould. The base of the mould was cooled by water spray. The copper mould was tilted at 1, 2 and 3o. The as-cast aluminum alloy bars were tested in accordance with ASTM standards to determine their mechanical properties, namely hardness and tensile strength. The results show that decreasing the mould tilt angle increases the mechanical properties of the as-cast aluminum-silicon alloy bars.